LEGAL PROTECTION OF CONSUMERS IN E-COMMERCE TRANSACTIONS BASED ON LAW NUMBER 11 OF 2008 CONCERNING INFORMATION AND ELECTRONIC TRANSACTIONS AND LAW NUMBER 8 OF 1999 CONCERNING CONSUMER PROTECTION LEGAL - Santy Santy (Faculty of Science and Technology University of Pramita Indonesia, 2023)
E-commerce is a form of trade that has its own characteristics, namely trade that crosses national borders, does not meet sellers and buyers, using internet media. The enactment of Law Number 11 of 2008 concerning Information and Electronic Transactions (UU ITE) seems to be a solution to provide protection for consumers. The ITE Law has regulated the legal requirements for an e-commerce transaction, regulates rights and obligations, prohibited actions, responsibilities, legal protection, legal remedies and dispute resolution in transactions. This research uses the method normative juridical approach with descriptive analytical research specifications. In addition to describing circumstances, objects or events, this research also discusses certain beliefs which are inferred based on the object of the matter associated with legal theories and positive legal practices. Primary and secondary legal data, which are collected and classified through library research techniques, are attempted to become a unified whole. Furthermore, the data is analyzed qualitatively so that clarity and answers are obtained about the issues that are the object of research. The results show that legal protection for online shopping consumers can be given in terms of legal certainty contained in the laws and regulations governing online shopping, namely Law no. 11 of 2008 concerning Information on Electronic Transactions juncto Law No. 8 of 1999 concerning Consumer Protection. In addition, the existence of electronic contracts as regulated in Article 18 (1) of the ITE Law is recognized and has the same position as conventional buying and selling contracts. E-commerce itself is a trading process that has its own characteristics where a trade can cross national borders, even without the seller and buyer meeting, by using the internet as a facilitator. On the one hand, this situation is quite profitable for the consumer, because there are many ways to choose from to obtain goods or services. However, from the other side, we see many violations of consumer rights that occur in e-commerce, which indeed has its own characteristics. Therefore a form of legal protection for consumers in e-commerce transactions is needed. Legal protection for business people, both sellers of services or goods as well as consumers, is regulated in Law Number 8 of 1999 concerning Consumer Protection and wrapping the process for what happens in cyberspace transactions, we call e-commerce, which also has rules, namely in Law Number 11 of 2008 concerning Information and Electronic Transactions. The methodology in this study uses normative, for normative itself this is discussed based on laws that apply directly to the general public. Based on these matters, it can be concluded that first, Law number 8 of 1999 and Law number 11 of 2008 can protect and provide rules of the game in the world of online business, which can regulate both consumers and business people.